The Waiting Room - Berland, Jackson (Kansas State University. Dept. of Music, Theatre, and Dance, 2020)
This 10-minute playattempts to answer what truly makes life worth living. Through the eyes of ayoung man who recently suffered a fatal car accident, this story follows theemotional journey of this man coming to terms with how he spent his life onEarth.
Kirmser Undergraduate Research Award - Individual Freshman category, honorable mention
Keywords: Play; Vehicle Accident; Examined Life; Philosophy; Purgatory